Potret Pembelajaran Pendidikan Islam Pada Anak Tunagrahita Di Sekolah Luar Biasa Bhakti Pemuda Kota Kediri - Novie Putri Amalia; Makhfud (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
This article discusses how the learning of Islamic Religious Education for mentally retarded children in Extraordinary Schools (SLB). Extraordinary Schools (SLB) are special schools for school-age children who have